Konstruksi Subjektivitas Bisri Mustafa terhadap Kitab Syarah Hadis Al Azw̄adu Al Musțafawiyah - Lailiyatun Nafisah (Al-Hasyimi: Jurnal Ilmu Hadis, 2024)
Several contemporary scholars have conducted studies on local sharia. Studies on the interaction between text and its surrounding context is endlessly. The book of Al Azw̄Adu Al Musțafawiyah is the work of Kiai Bisri Mustafa, who is known as an Indonesian scholar. In writing the book, there are influential elements, also known as subjectivity. To answer the subjectivity of kiai Bisri Mustafa in his book, the author uses Pierre Bourdieu's theory regarding habitus, capital and realm. This research is included in library research, in which the primary reference is Al Azw̄adu Al Musțafawiyah,, then supported by data sources from books, journals and other related writings. The research results show that Habitus consists of people's habits in speaking Javanese and a religious environment since childhood. Capital, which consists of mastery of the Javanese language, then travel and his experience since childhood in studying religious knowledge, became Kiai Bisri's capital in writing the book of Al Azw̄Adu Al Musțafawiyah. Domain, in this case the environment influences the translation model and meaning of gandul, colonial conditions, and the Javanese climate which influence Javanese traditions in the syarah. The existing elements have formed the subjectivity construction of Kiai Bisri Mustafa in writing the book Al Azw̄Adu Al Musțafawiyah.